2013
DOI: 10.1158/1078-0432.ccr-13-0320
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 Predicts the Presence of Lymph Node Metastases and Survival in Patients with Lung Adenocarcinoma

Abstract: Purpose We performed genome-wide microRNA-sequencing (miRNA-seq) in primary cancer tissue from lung adenocarcinoma patients to identify markers for the presence of lymph node metastasis. Experimental Design Markers for lymph node metastasis identified by sequencing were validated in a separate cohort using QPCR. After additional validation in the TCGA dataset, functional characterization studies were performed in vitro. Results MiR-31 was upregulated in lung adenocarcinoma tissues from patients with lymph … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 52 publications
4
102
0
1
Order By: Relevance
“…However, miR-31 was recently shown to be upregulated in lymph node metastases of patients with lung adenocarcinoma and in lung tumors of cyclin E transgenic mice (21,22). These conflicting ation in the miR-31-overexpressing cells was completely inhibited with expression of RASA1, SPRED2, SPRY1, or SPRY4, whereas SPRED1 expression partially inhibited proliferation ( Figure 7F).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, miR-31 was recently shown to be upregulated in lymph node metastases of patients with lung adenocarcinoma and in lung tumors of cyclin E transgenic mice (21,22). These conflicting ation in the miR-31-overexpressing cells was completely inhibited with expression of RASA1, SPRED2, SPRY1, or SPRY4, whereas SPRED1 expression partially inhibited proliferation ( Figure 7F).…”
Section: Discussionmentioning
confidence: 93%
“…This KRAS mouse model is known for not producing distant metastases, despite developing a large lung tumor burden with high-grade carcinoma (33). Consequently, we cannot exclude the possibility that miR-31 also contributes to lung cancer metastasis, as elevated levels of miR-31 were associated with patients with lung adenocarcinoma with lymph node metastasis, and this correlated with decreased survival (22). Increased miR-31 levels are also associated with advanced colorectal cancer and lung squamous cell carcinoma and correlated with decreased survival of patients with lung squamous cell carcinoma (18,19).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…miRNAs may act as either oncogenes or tumor suppressors according to the function of the target gene. In terms of NSCLC, in vitro functional assays have shown that miR-31 and miR-196 promote the proliferation, invasion and migration of cancer cells (10,11). Clinical analysis demonstrated that decreased miR-375 and increased miR-21 expression in NSCLC tissues are associated with advanced clinical stage and poor prognosis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…With this approach they detected 76 previously unknown miRNAs and 41 novel mature forms of known precursors, as well as 39 miRNAs significantly altered in cancer patients. Recently, a miRNA-sequencing (miRNA-Seq) study was conducted using SOLiD platform in ten fresh-frozen tumor samples from lung ADC patients [72]. The investigators found that miR-31 was up-regulated in patients with lymph node metastasis, compared with those without lymph node metastasis.…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%